FINANCIAL FEASIBILITY OF FOOD PROCESSING INDUSTRY: LESSONS FROM TOFU INDUSTRY IN TRUNAN VILLAGE, MAGELANG - Jalunggono, Gentur; Islami, Fitrah Sari; Hutajulu, Dinar Melani; Juliprijanto, Whinarko (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
This study aims to examine the financial analysis of the Food Processing Industry in Tofu Center of Trunan Village in an effort to maintain the calculation of operational costs, profit and loss, and investment in minimizing investment losses. In particular, this study aims to calculate the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI) in the Processed Food Industry in the Tofu Center of Trunan Village. The urgency of this research is to maintain the sustainability of the tofu industry in Trunan Village, which is one of the leading MSME centers in Magelang City and in an effort to maintain food security. Based on the results of the analysis it was found that financially the MSME management in the Tofu Center Food Processing Industry in Trunan Village did not fulfill the feasibility aspect. Net Present Value (Rp 2,147,030,794), Internal Rate of Return shows 2%, Payback Period 2 Years 8 months, and Profitability Index 4.10. Keywords: Feasibility Study, NPV, IRR, PP, PI